MARKET REACTION OF STOCKS LISTED ON THE JAKARTA ISLAMIC INDEX (JII) TO THE ANNOUNCEMENT OF THE 2017 GOVERNOR OF DKI JAKARTA - Sukmaningrum, Puji Sucia; Madyan, Muhammad; Hendratmi, Achsania (Universitas Airlangga, 2019)
The purpose of this research is to analyze the reaction of investors before and after the announcement of the determination of the Governor of DKI Jakarta in 2017 against abnormal return and trading volume of activity. These studies use quantitative methods of event study. Estimation period is 60 days and research period is 10 days before and 10 days after the announcement. the sample of this research is 30 stocks listed on the Jakarta Islamic Index (JII). The results showed no significant difference against AAR and ATVA before and after the announcement. Investor it is possible already to react before the official announcement of the Election Commission (KPU). Investors could do predictions the election results of the Survey or the quick count.Keywords: Market Reaction, Event Study, Abnormal Return, Trading Volume Activity, Islamic Capital Market.